Rear floor natural gas vehicle platform - Sahari, Barkawi; Mohd Yusoff, Rosnah; Wong, Shaw Voon; Ahmad, Mohd Fauzy; Kamaruzaman, Mohd Idzwan (2009)
A vehicle rear floor platform for a gaseous fuel systems such that it can accommodate fuel piping and tanks in transverse direction with all gas tanks (16) mounted underneath the platform supported by means of snug fit components fitted to the rear floor mounting bar (17) using means of detachable fastener and mounted to the rear floor panel (2) using welding, and the gas tanks (16) are arranged for ease of assembly, disassembly, maintenance, inspection, service, replacement and carters for the provision of fitting rear seats above the tank compartment allowing a sufficient head clearance for 95th percentile of Japanese male.